Faktor Risiko Kejadian Diabetes Melitus Tipe 2 Pada Pasien Rawat Jalan Di RSUD Sanjiwani Gianyar - Rama Dwi Suputra, I Gusti Lanang; Budiyasa, Dewa Gde Agung (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
Diabetes mellitus (DM) is a chronic disease characterized by increased blood glucose levels and is the fourth leading cause of death worldwide. The majority of diabetes mellitus sufferers worldwide are type 2 DM. The prevalence of DM continues to increase due to multifactorial changes in people's lifestyles and eating patterns. This study aimed to determine the risk factors associated with type 2 DM in outpatients at Sanjiwani Hospital, Gianyar. It was case-control with a consecutive sampling technique. The number of samples was 138 people, and they were analyzed using the Chi-Square test. Data was collected by interview and physical examination. The results of the analysis showed that the variable age > 45 years old with OR 2,438 (p-value = 0,003; 95% CI 1,491–5,923), gender or sex with OR 0,872 (p-value 0,711; 95% CI 0,422- 1,802), family history of DM with OR 4,219 (p-value 0,003; 95% CI 1,443–4,887), obesity with OR 2,278 (p-value 0,017; 95% CI 1,152-4,503), history of hypertension with OR 2,119 (p-value 0,035; 95% CI 1,049 – 4,280), less physical activity with OR 2,412 (p-value 0,014; 95% CI 1,188-4,900) and smoking with OR 0,779 (p-value 0,541; 95% CI 0,349- 1,737). In conclusion, a family history of DM, obesity, hypertension, and lack of physical activity were significant risk factors for the incidence of type 2 diabetes mellitus in Sanjiwani Hospital, Gianyar.